Statistical literacy from the Quechua workbooks - Pérez Taxi, Juliana (2025)
This study1 analyzes the statistical content in the mathematics workbook Yupana, designed for first-grade primary school students in Intercultural Bilingual Education (EIB) institutions in Peru. Statistical knowledge is presented in the National Curriculum of Basic Education (CNEB) as the competency called «Solve data management and uncertainty problems» according to the Ministry of Education of Peru (MINEDU, 2017). This article aims to describe the degree of statistical literacy embedded in the learning activities proposed in the workbooks, considering the Quechua language of the Chanka variety. To achieve this, a statistical content activity from the workbook is analyzed using the Problem, Plan, Data, Analysis, and Conclusion (PPDAC)cycle approach, alongside the ethnomathematical approach, to relate the intercultural context to statistical knowledge. The workbooks in quechua contain texts with statistical terminology, as well as texts that, although they do not include specific statistical terms, promote the development of statistical thinking and, consequently, statistical literacy. The study results will outline the degree of mediation required by EIB teachers to help bilingual students construct the meanings of statistical concepts through the activities proposedin the workbooks.